2008
DOI: 10.1103/physrevb.78.184302
|View full text |Cite
|
Sign up to set email alerts
|

Quantum cutting effect inKY3F10:Tm3+

Abstract: A cross-relaxation energy-transfer scheme using the 5d state of Tm 3+ as the donor and the 4f 13 states of Tm 3+ as the acceptor is proposed. The scheme is tested in the host KY 3 F 10 doped with several concentrations of Tm 3+ as a potential vacuum ultraviolet ͑VUV͒ excited blue phosphor of quantum yield greater than unity. Emission and diffuse reflection spectra along with studies of the time evolution of the 5d and 4f populations of Tm 3+ in KY 3 F 10 crystals and powders under UV and VUV excitations are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In LaP 3 O 9 and LaP 5 O 14 no red emission was detected under excitation at high energy below 150 nm although the absorption was very strong. No VUV emission was detected either, like in the case of KY 3 F 10 :Tm 3+ [26]. This is a very unusual behavior which was already observed [27].…”
Section: Vacuum Ultra-violet Spectroscopymentioning
confidence: 60%
“…In LaP 3 O 9 and LaP 5 O 14 no red emission was detected under excitation at high energy below 150 nm although the absorption was very strong. No VUV emission was detected either, like in the case of KY 3 F 10 :Tm 3+ [26]. This is a very unusual behavior which was already observed [27].…”
Section: Vacuum Ultra-violet Spectroscopymentioning
confidence: 60%
“…Actually, it was reported that YF 3 :Pr 3 þ shows 4f-4f emission from 1 S 0 [38,39]. In Nd 3 þ and Tm 3 þ doped YAlO 3 , many luminescence peaks were observed by various 4f-4f transitions [40][41][42][43][44][45][46][47]. Some UV luminescence peaks in the Nd 3 þ and Tm 3 þ samples were observed mainly from the emission levels of 2 G(2) 9/2 and 3 P 0, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…Micro-or nano-sized powders containing Tm 3 þ alone [4,5] or in combination with other rare earth ions [6,7] are interesting materials for developing blue and white phosphors. In this connection it has to be pointed out the recent and continuously growing interest towards Tm 3 þ -based phosphors with quantum yield greater than 1 to be used in plasma display panels (PDPs) and mercury-free fluorescent lamps [8]. These materials operate by a process called quantum cutting (QC) and require large bandgap host lattices suitable for UV and VUV excitations [9].…”
Section: Introductionmentioning
confidence: 99%